Correlation between tibial valgus deformity and aspect ratio of resected tibial surface in female Chinese patients undergoing total knee arthroplasty - Yang, Dejin; Wu, Xiang-Dong; Zhou, Yixin; Yin, Xinghua; Huang, Yong; Shao, Hongyi; Tang, Hao (Frontiers in Surgery, 2023)
Background: Morphology of the resected tibial surface is the reference for tibial component design, selection, and implantation in total knee arthroplasty (TKA). This comparative study sought to answer whether valgus deformity of the tibia would affect the morphology of the resected tibial surface in TKA. Methods: Thirty-one female Chinese patients with valgus tibias were retrospectively and consecutively identified from a single-center registration database. Thirty-one patients with well-aligned tibias were matched in terms of gender, height, and weight. Weight-bearing full-length radiographs and computed tomography images of the whole lower limb were obtained for every case. Tibial resection was mimicked perpendicular to the mechanical axis of the tibia in the frontal plane with 3° of posterior slope and a cut level individualized by the actual intraoperative cut. On the resected surface, mediolateral dimension (MLD), medial anteroposterior dimensions (mAPD), and lateral anteroposterior dimensions (lAPD) were measured, and aspect ratios (AR) were calculated. We compared the AR between the two groups. Results: The aspect ratio of resected tibial surface positively correlated with tibial valgus alignment. Patients with valgus tibias had significantly smaller AR (MLD/mAPD) for the medial plateau (1.50 ± 0.06 versus 1.54 ± 0.07, P = 0.032). However, the AR for the lateral plateau was similar between the two groups (1.63 ± 0.08 versus 1.65 ± 0.07, P = 0.328). Conclusions: This difference in morphology of resected tibial surface between valgus and well-aligned tibias should be considered in tibial component design, as well as in the selection and placement of TKA implants for knees with valgus tibias.